ENT 530 Social Media Portfolio: Banaynay / Nur Amirah Aqilah Azmi - Azmi, Nur Amirah Aqilah (2021)
Banaynay is a business that will produce a unique and different product for the market to change their trend of the people from vegetable snacks to fruit snacks. I will provide a real banana taste to my targeted customers to fulfill their maximization level of satisfaction. I will offer this new trended product at an affordable price for the customer benefit. Furthermore, I believe that my product is marketable among my targeting customers such as students and travellers.